Innovative vision rehabilitation method for hemianopsia: Comparing pre- and post audio-luminous biofeedback training for ocular motility improving visual functions and quality of life - Misawa, Mariana; Pyatova, Yulia; Sen, Atri; Markowitz, Michelle; Markowitz, Samuel N.; Reber, Michael; Daibert-Nido, Monica (Frontiers in Neurology, 2023)
Background Homonymous hemianopsia (HH) corresponds to vision loss in one hemi-field secondary to retro-chiasmal injury. Patients with HH experience difficulties in scanning and orientation in their environment. Near vision daily activities such as reading can also be impaired. There is an unmet need for standardized vision rehabilitation protocols for HH. We investigated the effectiveness of biofeedback training (BT), used for vision rehabilitation in patients with central vision loss, in individuals with HH. Methods In this prospective pilot pre/post study, 12 participants, with HH consecutive to brain injury, performed 5 weekly BT sessions for 20 min each under supervision using the Macular Integrity Assessment microperimeter. BT consisted of relocation of the retinal locus 1–4° toward the blind hemi-field. Outcomes measured post-BT were paracentral retinal sensitivity, visual acuity (near vision), fixation stability, contrast sensitivity, reading speed, and visual functioning questionnaire. Statistical analysis was performed using Bayesian paired t-tests. Results Paracentral retinal sensitivity significantly increased by 2.7 ± 0.9 dB in the treated eye in 9/11 of the participants. Significant improvements with medium-to-large effect size were observed for fixation stability (8/12 participants), contrast sensitivity (6/12 participants) and near vision visual acuity (10/12 participants). Reading speed increased by 32.5 ± 32.4 words per minute in 10/11 participants. Quality of vision scores improved significantly with large effect size for visual ability, visual information and mobility. Conclusion BT led to encouraging improvements in visual functions and functional vision in individuals with HH. Further confirmation with larger trials is required.